Pemanfaatan Aplikasi Google Family Sebagai Alat Pengawasan Penggunaan Smartphone Android Bagi Anak Di Desa Muliorejo Kecamatan Sunggal Kabupaten Deli Serdang - Seprida Hanum Harahap; Nadia Ika Purnama (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
information and communication technology has developed rapidly so that it becomes a necessity for anyone and even in professionalism, work is required to use information technology devices. Information technology devices in question include smartphones, laptops, smartwatches and so on. In line with that, data communication such as the internet, which is part of the device, is a primary need so that individuals can communicate without distance and time limitations. Google, as the largest company engaged in information technology, especially software development, develops special services to help children use smartphones safely and more purposefully, namely Google Family Link. Parents play an active role in controlling the use of their children's smartphone devices even though they cannot accompany them all the time. Muliorejo Village, Sunggal District, Deli Serdang Regency, through the PKK Team, as monitored by the author, saw the condition of children using smartphones without any restrictions, especially outside of school. Even outside of school hours until late at night, children are still found using these devices to play games outside of learning content.